Ketersediaan Obat Esensial pada Sarana Kesehatan di Kabupaten Bangka Barat - Achmad Nursyandi; Mustofa Mustofa; Mubasysyir Hasanbasri (Center for Health Policy and Management, 2012)
Background: The effectiveness of treatment at government health facilities is largely determined by the availability of the drug. In addition to essential drugs, doctors and the public can choose medications that are considered more suitable for medical needs. Bureaucratic rigidity and lack of funds the government plans to make the supply of medicines in health centers to be minimalist in terms of number and variety of drugs. Such inflexibility encourage minimalist prescribing behavior among primary care physicians and health workers. Objective: This study want to learn management practices that deal with drug supply and its distribution in government owned primary health care facilities. It specifically tried to identify strategies at health center level that allow the provision of more drugs in accordance with the medical needs and rational drug use practices. Method: Data were collected by observation report drug use and demand for health facilities in January-June 2010 and in- depth interview of chief health official, the head of pharmacy department, 7 of pharmacy main health centers and 11 midwives/nurses extending health center, village health clinic and village health post. Results: This case illustrates a successful story about making drugs available at primary health care facilities. Five main health centers, four extending health centers, and ten village health clinic and village health posts are classified as “safe” based on MOH standard. This success reflects human resource capacity and decentralized management of drug supply. Pharmacists and pharmacy assistants throughout the Bangka Barat Regency has already trained in drug supply management. The study also found that the procurement of drugs has been based on bottom-up planning. Although under the coordination of district level pharmacy unit, health care centers has broader authority to determine their drug needs. They also have their own drug procurement budget that are part of district budget that can be used for unexpected situations. Conclusion: This study attempted to show effort to change local government health sector bureaucracy in decentralization era. This case study shows the involvement and bigger participation of primary care facilities in the planning and implementation of drug supply. Health centers have a greater authority in managing the medication needs to circumstances beyond expectations. Communication, information and education to doctors about the drug delivery mechanism will allow doctors to prescribe drugs according to the medical needs of patients and drug development, and because it makes health care facilities into place an effective treatment. Latar Belakang: Efektivitas pengobatan di fasilitas kesehatan pemerintah sangat ditentukan oleh ketersediaan obat. Di samping obat esensial, dokter dan masyarakat dapat memilih obat-obat yang dipandang lebih cocok untuk kebutuhan medik. Kekakuan birokrasi perencanaan dan keterbatasan dana pemerintah membuat penyediaan obat di puskesmas menjadi minimalis dari sisi jumlah dan variasi obat. Kekakuan seperti itu mendorong praktik peresepan minimalis yang diragukan manfaat terapetiknya. Tujuan: Penelitian ini mempelajari manajemen penyediaan obat dan distribusinya di fasilitas kesehatan dasar. Ia secara khusus berusaha menemukan strategi-strategi di tingkat puskesmas yang membuat penyediaan obat lebih sesuai dengan kebutuhan lapangan dan pengobatan rasional. Metode: Data dikumpulkan dengan observasi laporan pemakaian dan permintaan obat sarana kesehatan bulan Januari-Juni 2010 dan wawancara mendalam terhadap kepala dinas kesehatan, kepala instalasi farmasi, 7 pengelola obat puskesmas dan 11 bidan/perawat pustu, polindes serta poskesdes. Hasil: Penelitian ini menunjukkan bahwa lima puskesmas, empat puskesmas pembantu, dan sepuluh polindes dan poskesdes berhasil merencanakan dan menyediakan obat hingga pada tingkat yang “aman”. Keberhasilan ini merupakan bukti dari kapasitas tenaga yang memadai. Apoteker dan seluruh pengelola obat puskesmas Kabupaten Bangka Barat sudah memiliki mengikuti pelatihan manajemen pengelolaan obat. Penelitian juga menemukan bahwa pengadaan obat telah berbasis desentralisasi dan mencerminkan perencanaan bottom up. Meski di bawah koordinasi instalasi farmasi kabupaten, puskesmas memiliki kewenangan menentukan kebutuhan. Mereka juga memiliki fleksibilitas pengadaan obat sendiri untuk situasi di luar dugaan. Kesimpulan: Penelitian ini berusaha memperlihatkan upaya perubahan birokrasi di bidang kesehatan dalam era desentralisasi. Studi kasus dalam penyediaan obat esensial di Kabupaten Bangka Barat menunjukkan keterlibatan dan partisipasi puskesmas yang lebih besar dalam perencanaan dan implementasinya. Puskesmas juga memiliki kewenangan lebih besar dalam mengelola kebutuhan obat untuk situasi di luar dugaan. Komunikasi, informasi dan edukasi kepada dokter tentang mekanisme penyediaan obat akan memudahkan dokter meresepkan obat sesuai dengan kebutuhan medik pasien dan perkembangan obat, dan karena itu membuat fasilitas kesehatan menjadi tempat pengobatan yang efektif.